<h3> zor bir soru cevap Ceyhan</h3>
8x + 7y = 39
4x - 14y = -68
(multiply each term in second equation by -2)
8x + 7y = 39
-8x + 28y = 136
(add both equations)
35y = 175
(divide both sides by 35)
y = 5
(substitute value of y in one of the equations)
8x + 7(5) = 39
8x + 35 = 39
8x = 4
x = 1/2
(x, y) = (1/2, 5)
Option D is the correct answer
Answer:
(2n+6)^2
Step-by-step explanation:
To solve this, you can use the given formula: x^2 + 2xy + y^2
In this case, 4n^2 is x^2, 24n is 2xy, and 36 is y^2. The next step is:
(2n)^2 + 2(2n)(6) + (6)^2
Since this equation fits into this formula ( x^2 + 2xy + y^2), we can do:
(2n+6)(2n+6) =
(2n+6)^2
Hence, the answer is (2n+6)^2